Making the Case for Doctoral Student Success Through Group Advising and Dissertations - Diane D Chapman; Michelle Bartlett (Adult Education Research Conference, 2018)
Many adult doctoral students at dissertation stage are isolated and unable to focus. Group advising and group dissertation work may combat barriers to completion and lead to greater student success.
Keywords: Advising; Higher Education; Dissertations